The mummy - Abdo, Kenny, 1986- (Minneapolis, Minnesota : Bolt!, an imprint of Abdo Zoom, 2019)
Explores the history of the mummy, including the movie adaptations.
Includes index.
5.5
5-8
780L
Keywords: Mythology -- Juvenile literature; Monsters in literature -- Juvenile literature; Mythology; Monsters in literature